Membongkar Rahasia Penelitian: Metode Sederhana dan Mudah Dilakukan - Rina Amelia; Doni Prabowo; Isna Wati (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Research is one of the means to achieve change, growth and development. This article covers aspects of research methodology, discusses the basic principles of research, and the steps needed to make research with simple and easy-to-conduct methods. This webinar aims to educate, introduce and popularize simple but effective research methods, so that they can encourage social change in research practice. In the implementation of the webinar, information was obtained based on the results of questions and answers, presentations of resource persons who are experts in the field of research and various relevant literature sources. The indicators that became the subject of discussion in the webinar included information on how to carry out research by determining methods, data collection techniques, data analysis techniques, writing research reports and ethics in research. During the research process, AI tools such as Quillbot, Turnitin, Mendeley, and ChatGPT can be used to facilitate and support researchers. These tools can help with tasks such as generating ideas and suggestions, organizing and analyzing data, checking for plagiarism, and generating text and summaries. By using these tools, researchers can save time and effort, improve research quality, and productivity. The research process can be further improved by using simple methods and techniques based on literature reviews, online surveys, and virtual-based interviews.